Kako s pomočjo uporabe interaktivne table razvijati učne strategije za učinkovitejše učenje besedišča v tujem jeziku? - Retelj, Andreja (Vestnik za tuje jezike, 2011)
The article focuses on some possibilities of using the available materials on the interactive board, which can contribute to the development of the learning strategies and to the quality as well as to the efficiency in the process of vocabulary learning. The current findings on learning strategies and vocabulary learning (Oxford 1990, Nunan 1999, Nation 2001) are combined and compared to the usage of various materials of i-board in the classroom. A meaningful usage of i-board being our priority, we found more advantages in the use of i-board in comparison to the classical exercises on the paper. Our material is based on Piepho's and Häussermann's typology of exercises for improving vocabulary learning. The students' perception of the interactive board in classroom is included and is based on analysis of the results of an online survey of 58 students, who had been using interactive board in German language classes for two years.
Keywords: tuji jeziki; besedišče; interaktivna tabla; učne strategije; tipologija vaj in nalog; didactic method; didaktika; metodika